Determinants of Implementation of Government Accounting Standards in the Binjai City Government - Ramadhan, Puja Rizqy; Nasution, Dito Aditia Darma; Sinuraya, Raissa Gloriana Br. (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The purpose of this study was to determine the effect of the Quality of Human Resources, Organizational Commitment and Quality of Information Technology on the Implementation of Government Accounting Standards in the Binjai City Government. The location of the research was carried out at the Regional Revenue and Asset Financial Management Agency (BPKPAD) of Binjai City. The population in this study were employees of the accounting sub-sector who had status as Civil Servants and served for at least one year at the Regional Revenue and Asset Financial Management Agency, namely as many as 14 people. The hypothesis was tested using multiple linear regression analysis. The results of this study indicate that the Quality of Human Resources, Organizational Commitment and Quality of Information Technology simultaneously have a significant effect on the Implementation of Government Accounting Standards in the Binjai City Government. Partially, the Quality of Human Resources and Quality of Information Technology has a positive and significant effect on the Implementation of Government Accounting Standards, while Organizational Commitment has a negative effect on the Implementation of Government Accounting Standards in Binjai City.